2 - Religious citizenship: The case of the globalised Khoja - Iqbal S. Akhtar, (African Sociological Review, 2015)
The African Khōjā are an Indic Muslim caste, which began migrating from Sindh and Gujarat to East Africa in the late 18th century. During the 19th and 20th centuries, their economic success in an institutionally underdeveloped region coupled with a strong religious impetus allowed them to build communal municipal institutions throughout the region that both mimicked and replaced the absent state. The insecurity of postcolonial East Africa, such as the 1964 revolution in Zanzibar and the 1972 Ugandan Asian exodus, forced the Khōjā to further expand their bureaucratic apparatus towards foreign policy- migration to Western Europe and North America and requisite institutionalization. In the 21st century, the Khōjā coordinate these communal networks from North America and Western Europe to Asia and Africa towards a religious based economic development in emerging economies. Their primary identity is religious, defined from within and outwith, using the mechanisms of globalization to further communal aims internationally within a framework of religious nationalism insensible to state nationalism.